2014
DOI: 10.1589/jpts.26.1895
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hip Joint Position on Muscle Activity during Prone Hip Extension with Knee Flexion

Abstract: [Purpose] This study investigated the selective activation of the gluteus maximus during a prone hip extension with knee flexion exercise, with the hip joint in different positions. [Subjects] The subjects were 21 healthy, male volunteers. [Methods] Activities of the right gluteus maximus, right hamstrings, bilateral lumbar erector spinae, and bilateral lumbar multifidus were measured using surface electromyography during a prone hip extension with knee flexion exercise. Measurements were made with the hip joi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…On the other hand, s-GMax EMG activity with PR-Ext-ER was significantly higher than that with PR-Ext and PR-Ext-IR. This finding is the same as in a previous study 14 ) , which observed increased GMax activity during extension in external rotation in comparison with that during extension in a neutral hip joint position. In other words, shortening GMax by externally rotating the hip joint is a means of increasing activity.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, s-GMax EMG activity with PR-Ext-ER was significantly higher than that with PR-Ext and PR-Ext-IR. This finding is the same as in a previous study 14 ) , which observed increased GMax activity during extension in external rotation in comparison with that during extension in a neutral hip joint position. In other words, shortening GMax by externally rotating the hip joint is a means of increasing activity.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, subjects abducted the hip prior to and during performance of PHEKF exercise, which led to GM activation as a hip abductor, and this increased its responsiveness during PHEKF relative to position N. GM onset relative to the hamstrings was also significantly earlier in the ABER position than in the AB position. Previous work demonstrated that because external rotation of the hip in PHEKF exercise reduces the amount of hamstring muscle activity and the hip extension moment that can be exerted by the hamstrings, the GM is more active as an extensor compared with the hamstrings 17 ) . Therefore, the relative onset time of the GM as a driving force for hip extension in position ABER seems to have occurred earlier.…”
Section: Discussionmentioning
confidence: 99%
“…The starting position for HEXT was in a standing-prone position at 608 of hip flexion. [12][13][14] Participants were instructed to extend the tested leg until it was parallel to the long axis of the torso, and then they were positioned in 308 of abduction, 208 of external rotation, and 908 of knee flexion, which is often called a donkey-kick The nontest leg was in contact with the floor and the knee slightly bent for stability. The starting position for HAB was side lying with the nontest leg in 308 of hip and knee flexion and the test leg parallel with the long axis of the torso.…”
Section: Methodsmentioning
confidence: 99%